Factors Affecting The Incidence of HIV/AIDS Based on Region in Pati Regency on 2017 (Public Health Perspective Journal, 2018)
Multi faktor yang mempengaruhi peningkatan kasus HIV/AIDS di Kabupaten Pati adalah perilaku seksual, konsistensi penggunaan kondom, sosioekonomi, kunjunganÂ  ke tempat lokalisasi, akses ke tempat pelayanan kesehatan,perilaku seks pada pasangan, riwayat HIV/AIDS pada pasangan. Metode penelitian adalah purposive sampling dengan desain case control Populasi Semua orang yang sudah melakukan tes HIV berdasarkan data klinik VCT RSUD RAA Soewondo Pati dan sampel sejumlah 122 sampel diperoleh dengan rumus lameshow. Instrumen yang digunakan adalah kuesioner. Data analisis menggunakan uji Chi Square dengan derajat kemaknaan 5% (Î±=0,05).Multi factors that influence the increase of HIV / AIDS cases in Pati District are sexual behavior, consistency of condom use, socioeconomic, visit to localization, access to health service, partner sexual behavior, history of HIV / AIDS in couples. Methods of the study were observational analytic with case control design Population All people who had tested HIV based on VCT clinic data RSUD RAA Soewondo Pati and sample of 122 samples were obtained by lameshow formula. The instrument used is a questionnaire. Data analysis using Chi Square test with degree of significance 5% (Î± = 0,05).The result of research shows the western region in Pati Regency there is relationship between sex behavior with the incidence of HIV / AIDS with the value of OR 21,0 (p = 0,006), there is correlation between injection drug usage with the incidence of HIV / AIDS with value OR = 36,0 (p = 0.002). In the north there is a relationship between sex behavior with the incidence of HIV / AIDS with the value of OR 21.2 (p = 0.001), there is a relationship between socioeconomic to HIV / AIDS incidence with OR = 10,0 (p = 0,002) and there is a relationship between history of HIV / AIDS in family OR = 6,2 (p = 0,015) with HIV / AIDS incidence. In the southern region of Pati Regency there is a relationship between socioeconomic and HIV / AIDS incidence with an OR value of 13.4 (p = 0.002) and there is a family history of HIV / AIDS with HIV / AIDS incidence with OR = 15.0 (p = 0.002 ). In the eastern region of Pati Regency there is a relationship between socioeconomic and HIV / AIDS incidence with an OR value of 12.0 (p = 0.010).